Objective structured clinical examination in fundamentals of nursing and obstetric care as method of verification and assessing the degree of achievement of learning outcomes - Sochocka, Lucyna; Niechwiadowicz-Czapka, Teresa; Wojtal, Mariola; Przestrzelska, Monika; Kiersnowska, Iwona; Szwamel, Katarzyna (Nursing in the 21st Century, 2021)
OBJECTIVE STRUCTURED CLINICAL EXAMINATION IN FUNDAMENTALS OF NURSING AND OBSTETRIC CARE AS METHOD OF VERIFICATION AND ASSESSING THE DEGREE OF ACHIEVEMENT OF LEARNING OUTCOMESAim. The aim of the study was (1) to assess the degree of preparedness of nursing and midwifery students for OSCE-type examinations (Objective Structured Clinical Examination), (2) to learn the opinions of students regarding examination in the form of the OSCE and (3) to learn about the emotions which accompany the examination.Material and methods. The number of 160 (53.33%) nursing students and 140 (46.67%) midwifery students from 5 medical universities were studied. The diagnostic survey method and survey techniques were applied. An own questionnaire was used.Results. Students were the best prepared to perform hygienic and nursing procedures (M=4.22, SD=0.85) and the least prepared to perform gastrointestinal procedures (M=3.03, SD=1.24). The majority (237/79%) claimed that the OSCE examiners should be lecturers from their home university. High marks were given to the quantity and quality of equipment prepared for the examination (232/77.34%) and knowledge of the rules and procedure of conducting the examination (226/75.33%). The OSCE examination was accompanied by high levels of stress (M=4.64, SD=0.78) and fear of making a mistake (M=4.54, SD=0.75). One of the lowest rated aspects of the OSCE exam by students was the time allocated to completing tasks (M=2.96, SD=1.21).Conclusions. Because students rated low the time allocated to the tasks, the lecturers organizing the examination in the future should pay more attention to this aspect. From the very first semester, it is worth considering the introduction of classes in nursing and midwifery aimed at teaching effective ways of coping with stress.